Efficacy and safety of duloxetine in osteoarthritis or chronic low back pain: a Systematic review and meta-analysis. Issue 6 (June 2020) - Weng, C.; Xu, J.; Wang, Q.; Lu, W.; Liu, Z.
Summary: Objective: To evaluate the efficacy and safety of duloxetine in the treatment of patients with osteoarthritis (OA) or chronic low back pain (CLBP). Methods: Relevant randomized controlled trials (RCTs) were searched in PubMed, Embase, Web of Science, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov . Included RCTs compared the efficacy and safety of duloxetine vs placebo in the treatment of OA or CLBP. Weighted mean difference (WMD) were calculated for continuous outcomes while risk ratio (RR) were calculated for dichotomous outcomes. Results: Nine RCTs were included in our meta-analysis. Duloxetine had significant improvement over placebo in Brief Pain Inventory 24-h average pain [WMD: −0.67; 95% confidence interval (CI):-0.80, −0.53], weekly mean of the 24-h average pain (WMD: −0.65; 95% CI: −0.79, −0.52), Patient's Global Impression of Improvement (WMD: −0.41; 95% CI: −0.49, −0.32), Clinical Global Impression of Severity (WMD: −0.32; 95% CI: −0.38, −0.25), European Quality of Life Questionnaire-5 Dimension (WMD: 0.04; 95% CI: 0.02, 0.07). In addition, duloxetine is associated with more treatment-emergent adverse events (TEAEs) (RR: 1.25; 95% CI: 1.17, 1.33) and discontinuations for adverse events (AEs) (RR: 2.31; 95% CI: 1.81, 2.94). However, there was no statistically significant difference in serious AEs between duloxetine and placebo. Conclusion: Duloxetine had modest to moderate effects on pain relief, function improvement, mood regulation and improvement in quality of life with mild AEs in the treatment of OA or CLBP. Future RCTs should focus on comparing duloxetine with other oral drugs and assessing the long-term safety of duloxetine.